2011
DOI: 10.1074/jbc.m110.186817
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Alterations in RNA Editing Modulate Complex Behavior in Drosophila

Abstract: Select proteins involved in electrical and chemical neurotransmission are re-coded at the RNA level via the deamination of particular adenosines to inosine by adenosine deaminases acting on RNA (ADARs). It has been hypothesized that this process, termed RNA editing, acts to "fine-tune" neurophysiological properties in animals and potentially downstream behavioral outputs. However, the extreme phenotypes resulting from deletions of adar loci have precluded investigations into the relationship between ADAR level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 44 publications
(44 reference statements)
4
55
0
Order By: Relevance
“…1c). We have previously shown that the HA-tag has no effect on dADAR activity on several known targets 28 , and western blot analyses revealed that modifying auto-editing has no significant effect on levels of dADAR protein expression (Fig. 1d).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…1c). We have previously shown that the HA-tag has no effect on dADAR activity on several known targets 28 , and western blot analyses revealed that modifying auto-editing has no significant effect on levels of dADAR protein expression (Fig. 1d).…”
Section: Resultsmentioning
confidence: 82%
“…We recently engineered a novel hypomorphic allele of dAdar ( dAdar hyp ), in which dADAR expression is reduced by ~ 80% (ref. 28). In this background, editing at many sites, but not all, is significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ADAR substrates in Drosophila melanogaster (dADAR) appear to fall into “high” or “low” categories based upon structure and sequence determinants that affect their intrinsic ability to be selectively deaminated (Jepson et al, 2011). Higher levels of dADAR are required for the editing of “low efficiency sites”, whereas low levels of enzyme can effectively edit “high efficiency” sites.…”
Section: Discussionmentioning
confidence: 99%